THE IMPACT OF NPM, ROI, ROE AND CASH RATIO ON FINANCIAL DISTRESS (Study Of Manufacturing Companies In The Consumption Goods Industrial Sector Listed On The Indonesia Stock Exchange In 2019 - 2021) - Eugenio Eugenio; Angeline Angeline; Beatrix Patricia Lee; Herlin Munthe; Nasib Nasib (Jurnal Ekonomi, 2023)
Several factors, both internal and external to the organization, can be used to gauge financial performance. In order to determine whether the four ratio variables have an impact on financial distress at a firm, this study will examine how to measure the company's financial performance using NPM, ROI, ROE, and Cash Ratio. Multiple linear regression analysis and descriptive statistical analysis are both used in this study. The population is the financial statements of several manufacturing companies in the consumer goods industry sector, such as PT. Unilever Indonesia Tbk, PT. Mayora Indah Tbk, and PT. Kino Indonesia Tbk. for three years on the official website idx.co.id starting in 2019, 2020, 2021, and using a saturated sample where the entire population is sampled, which are the financial statements of the three companies from 2019 to 2021, calculated by quarterly reports. The research results show that Net Profit Margin has no significant impact on financial distress with the test results obtained the t-count value is -1.095 with a significance of 0.282 while the t-table is 1.69552 with a significance of 0.05. Return on Investment significantly positive impact on financial distress with the results of testing the t-count value of 2.886 with a significance of 0.007 with a t-table of 2.03951 with a significance of 0.05. Return on Equity significant negative impact on financial distress with the results of the t-count test -2.897 with a significance of 0.007 with a t-table of 1.69552 with a significance of 0.05. Cash ratio have a significant positive impact on financial distress in several manufacturing companies in the consumer goods industry sector for the period 2019 - 2021 with a t-count test result of 10.625 a significance of 0.001 with a t-table of 2.03951 a significance of 0.05. The results of the F-table test = 2.67 and an error rate of 5%, obtained an F-count value of 50.596 > F-table 2.67 with a significance of 0.002 <0.05, meaning that statistical testing simultaneously shows Net Profit Margin, Return on Investment, Return on Equity, and Cash Ratio all of which have a significant impact on financial distress in several manufacturing companies in the consumer goods industry sector for the period 2019 - 2021